PEMETAAN WILAYAH PRIORITAS PENINGKATAN AKSESIBILTAS SANITASI DALAM PERSPEKTIF RENCANA STRATEGIS PEMBANGUNAN SANITASI DI PROVINSI JAWA TENGAH - Maryono, Maryono (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2010)
Choosing  for  priority  areas  in  efforts  to  improve  sanitation  usually  determined  by various considerations such as technical, economic, social, cultural, community empowerment, and physical environment  in  the  study  area.  Consideration of the technical aspects will formulate about the availability  of  infrastructure  services.  Socioeconomic  considerations  explain  poverty,  income per capita. Socio-cultural considerations and community empowerment to explain about the culture, habits and  the  willingness  and  ability  of  communities  to  bersaniter.  While  the  physical environment considerations  explain  the  advantages  and  disadvantages  of  natural  physical  region, including  the potential occurrence of natural disasters and disturbances. this study is conducted to analysis on the Priority sanitation improvement that combines of social aspects such as economic considerations and technical aspect such as availability of facilities / infrastructure sanitation